2013
DOI: 10.1021/jp3118105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postannealing on the Photoluminescence Properties of Coprecipitated Nanocrystalline BaFCl:Sm3+

Abstract: Nanocrystalline BaFCl:Sm(3+), as prepared by coprecipitation from aqueous solutions, is an efficient photoluminescent X-ray storage phosphor. In the present study, we report effects on its photoluminescence properties resulting from postannealing treatment in air in the temperature range between 100 to 900 °C. Interestingly, upon annealing at temperatures from 200 to 600 °C in air, a small fraction of the Sm(3+) ions in nanocrystalline BaFCl can be reduced to Sm(2+) ions. In addition to the creation of Sm(2+) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Recently, another group of researchers has reported two sites of Sm 3+ in BaFCl sample during annealing treatment. These authors have suggested that the first site is possibly located at or near the crystallite surface, whereas the second site is situated in a very ordered environment (Zhiqiang et al 2013). In the present work, it is believed that part of the Sm 3+ ions might have entered into the lattice replacing Al 3+ ions and the rest might be located at the surface of ZnAl 2 O 4 .…”
Section: 1b Luminescence Decay Time Studiesmentioning
confidence: 52%
“…Recently, another group of researchers has reported two sites of Sm 3+ in BaFCl sample during annealing treatment. These authors have suggested that the first site is possibly located at or near the crystallite surface, whereas the second site is situated in a very ordered environment (Zhiqiang et al 2013). In the present work, it is believed that part of the Sm 3+ ions might have entered into the lattice replacing Al 3+ ions and the rest might be located at the surface of ZnAl 2 O 4 .…”
Section: 1b Luminescence Decay Time Studiesmentioning
confidence: 52%
“…Sm 3+ ion is widely used as an activator of reddish orange emission due to its 4 G 5/2 → 6 H J (J = 5/2, 7/2, 9/2, 11/2) transitions, which is the most suitable source for lighting and display from a practical viewpoint [13,14,15,16]. Based on the previous information, the YInGe 2 O 7 is chosen to be the host, and references concerning the role of the rare-earth Sm 3+ ion-doped in YInGe 2 O 7 have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…This is most likely due to the higher defect density in the nanocrystalline sample and microstructural arrangement of oxide impurities. A range of investigations on preparation conditions, luminescent and hole-burning properties, and the storage mechanism have been reported for this material. These results indicate that other divalent RE ions may also be generated readily by X-irradiation in the BaFCl host lattice.…”
Section: Introductionmentioning
confidence: 92%